FAKTOR – FAKTOR DETERMINAN KEJADIAN NEEDLESTICK INJURY PADA PERAWAT BAGIAN RAWAT INAP RS X, KOTA SEMARANG - Tomas Jalu Putranto; Yuliani Setyaningsih; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Needlestick Injury (NSI) as a wound caused by a needle that accidentally punctures the skin, it can be caused by needles such as hypodermic syringes, blood-taking needles, intravenous stylets, and connecting needles from the intravenous delivery system. The purpose of this study was to analyze the correlations between age, sex, years of service, education level, perception of risk, safe working training and nonstandard action with the incidence of needlestick injury on inpatient nurses in X Hospital, Semarang City. The type of this study is a descriptive analytic research with a cross-sectional study model. The sample in this study are 72 nurses inpatient section of X Hospital, Semarang City. The research instrument uses a questionnaire that has been tested for validity to determine the age, sex, work period, level of education, and participation in training to work safely and measure risk perceptions and nonstandard actions. The results of this study found that 21 nurses (29.9%) experienced needlestick injury in the last year and showed a corelations between age (sig 0.015), years of service (sig 0.001), and nonstandard action (sig 0.001) with needlestick injury incidence. There was no correlations between sex (sig 0.552), education level (sig 1,000), risk perception (sig 0.625), and work safe training (sig 0.271) with needlestick injury events. To prevent and reduce the incidence of needlestick injuries the hospital should review the SPO injection by paying more attention to needle recapping and the behavior of the use of safety boxes and reviewing the existing training system to make it more effective and efficient. The hospital should also improve data management regarding NSI to detect and suppress the needlestick injury incidence